AEG-1/MTDH: A central regulator of tumor progression, metabolic adaptation, and therapeutic resistance in gliomas - Suleiman Ibrahim Mohammad; Asokan Vasudevan; Mutaz Jamal Al-khreisat; Safa H. Radhie; Zukhra Yakhshieva; Ibrokhim Sapaev; Mirza R. Baig; Navin Kumar Tailor; Divya Singhal; Amr Ali Mohamed Abdelgawwad El-Sehrawy (Tissue and Cell, 2027)

MGMT promoter methylation across glioma subtypes: biological relevance, treatment response, and survival outcomes - Usamah Sayed; Rano Alieva; Malathi Hanumanthayya; Divya Singhal; Rajashree Panigrahi; Navin Kumar Tailor; Tulkin Buzrukov; Sirojiddin Norkulov (Molecular Biology Reports, 2026)

Human hepatic cell line 5: In-vitro model for hepatic immunobiology - Smeeta Shrestha; Ming Yue Yeong; Xin Yi Cheng; Wei Wang; Nidhi Bhayana; Navin Kumar Verma; Yongping Bao; Yulan Wang (Molecular Biology Reports, 2026)

Boronic acid-functionalized materials in food and environmental safety: Progress in design, synthesis, and sensing applications - Suleiman Ibrahim Mohammad; Asokan Vasudevan; Feras Alnaimat; Mirza R. Baig; Shreedhar M. Rao; Gulnoza Djakhangirova; M.M. Rekha; Navin Kumar Tailor; Sandeep Kumar Shukla; Zyad Shaaban (Journal of Environmental Chemical Engineering, 2026)

Food-derived dietary alkaloids: structure–biofunctionality relationships in modulating gut microbial biofilms for downregulation of colorectal carcinogenesis - Saikat Mazumder; Debasmita Bhattacharya; Dibyajit Lahiri; Moupriya Nag; Sudhriti Maity; Debpriya Saha; Navin Kumar; Vandana Singh; Shubham Sharma; Shashi Prakash Dwivedi; Mithul Rajeev; Seema Raj; et al. (Food Research International, 2026)

Cellular and Microenvironmental Functions of SNHG lncRNAs in Tumor Immune Remodeling - Tareq Nayef Alramadneh; Afaq Mahdi Ali; Fatima Muhammad Yunus; Pareshkumar N. Patel; K. Jamuna; Vandana Tripathi; Priya Priyadarshini Nayak; Navin Kumar Tailor (Tissue and Cell, 2026)

Aptamer-conjugated nanoparticles: emerging nano-enabled platforms for rapid and sensitive detection of viral infections - Harpreet Kaur Walia; Komal Choudhary; Navin Kumar (Archives of Microbiology, 2026)

Groundwater heavy-metal contamination and human health risks: carcinogenic, non-carcinogenic, and spatial hotspot assessment in a tribal region of central India - Prashant Sahu; Navin Kumar Verma; Vikas Kumar Jain; Nitin Kumar Jaiswal (Environmental Geochemistry and Health, 2026)

An investigation of the global responses of the thermal field of the MLT region to the ‘Severe’ geomagnetic storm of 10–11 October 2024 - Govind Narayanan Kunnath; Navin Parihar; Chinmaya Nayak; Alok Taori; Anand Kumar Singh; Shailendra Saini; Prasant Kumar Tiwari; Ashok Priyadarshan Dimri (Advances in Space Research, 2026)

Understanding the Role of fasciated 2, fasciated 4, tassel dwarf 1 and tassel sheath 4 Genes in the Manifestation of Grain Yield in Field Corn (Zea mays L.) - Bhargava Kotte; P. Bhavana; Ganapati Mukri; Raveendra N. Gadag; Jayant S. Bhat; Chandu Singh; Navin C. Gupta; K. V. Gowtham; Kumari Shilpa; Chandra Prabha; Santhosh Kumar (Indian Journal of Genetics and Plant Breeding, 2026)

Deciphering the geochemical signatures of groundwater quality dynamics in tribal landscapes of the Pairi River Basin - Navin Kumar Verma; Prashant Sahu; Vikas Kumar Jain; Nitin Kumar Jaiswal (Environmental Geochemistry and Health, 2026)

Comparative transcriptome analysis reveals underlying aggressiveness mechanisms of Sclerotinia sclerotiorum infecting Brassica juncea - Nitish Rattan Bhardwaj; J. S. Kushveer; Prashant Yadav; Hariom Kumar Sharma; Neeraj Budhlakoti; Dwijesh C. Mishra; Navin C. Gupta; Pankaj Sharma; Vijay Veer Singh (Archives of Microbiology, 2026)

Transglutaminase-assisted development of millet-legume-based mock meat - Riya Joshi; Umesh C. Lohani; Navin Chandra Shahi; Ashok K. Verma; Atul Singh; Iqbal Hussain; Sanjay Kumar (Food and Humanity, 2026)

Resistance-based exercise restores muscle health in dialysis patients - Piush Srivastava; Sunil Kumar Singh; Rakesh Sathish Nair; Saket Jha; Navin Viswakarma; Deepti Srivastava; Greg Hachaj; Stephen T. Bartlett; Ilaria Santi; Aslam Ejaz; Robert W. Motl; Enrico Benedetti; et al. (Journal of Muscle Research and Cell Motility, 2026)
Chronic kidney disease (CKD) and end-stage renal disease (ESRD) are serious health concerns worldwide that require regular dialysis before a kidney transplant for a better quality of life. Due to aging and frailty, dialysis patients are often limited in physical activity, which can lead to multiple health complications and sometimes result in patient death. Therefore, maintaining muscle health is crucial for individuals undergoing dialysis. We recently reported that personalized resistance-based exercise can improve frailty in dialysis patients; however, the molecular mechanisms underlying its effects on muscle health remain unknown. RNA-Seq analysis revealed that exercise upregulates genes associated with muscle stemness, regeneration, and differentiation. Furthermore, our study demonstrated that exercise upregulates mitochondrial proteins involved in the oxidation of organic compounds and mitochondrial function in muscle. Moreover, we observed that exercise increased energy production via glucose uptake, glycogenesis, and fatty acid metabolism. These results suggest that personalized resistance-based muscle therapy in dialysis patients restores the expression of genes and proteins associated with muscle stemness, regeneration, differentiation, and energy generation.

Unlocking the genetic and molecular secrets of thousand-seed weight in Indian mustard [Brassica juncea (L.) Czern. & Coss.] employing generation mean and candidate gene analysis - Manoj Kumar Patel; Masochon Zimik; Sneha Adhikari; Yashpal Taak; Navin C. Gupta; Joghee Nanjundan; K. K. Vinod; Sujata Vasudev; Devendra Kumar Yadava; Navinder Saini (Planta, 2026)

Soil Moisture Prediction Using Artificial Neural Networks and Remote Sensing Data - Aryan Singh; Avdhesh Kumar; Ankit Singh; Rohit Kumar Tiwari; Navin Chaurasiya; Adarsh Singh; Shashank Shekhar Singh; Manish Pratap Singh (Remote Sensing in Earth Systems Sciences, 2025)

A broad climatology of very high latitude ( ∼ 75 ° ) substorms: An update - Anand K. Singh; Navin Parihar; Shailendra Saini; Sunil Kumar; Rashmi Rawat; Vladimir Belakhovsky; Wojciech J. Miloch; Gopi Seemala; A.K. Sinha (Advances in Space Research, 2025)

Development of thymol-enriched basil oil nanoemulsions for management of tomato bacterial pathogens - Rahul Patidar; Malkhan Singh Gurjar; Ganesan Prakash; Kajal Kumar Biswas; Lokesh Babu P; Rashid Pervez; Parshant Kaushik; Navin Chandra Gupta; Dinesh Singh (Physiological and Molecular Plant Pathology, 2025)

CRISPR/Cas9: efficient and emerging scope for Brassica crop improvement - Shiv Shankar Sharma; Ashwani Pandey; Anamika Kashyap; Lakshay Goyal; Pooja Garg; Ranjeet Kushwaha; Jyoti Sharma; Shikha Tripathi; Sujata Kumari; George Thomas; Malkhey Verma; Navin C. Gupta; et al. (Planta, 2025)

Experimental and DFT studies of green synthesized ZnO nanoparticles for their antibacterial and optoelectronic applications - Satish Saw; Sunil Mahto; Mahendra Kumar; Navin Chandra; Lalit Kumar Sharma (Next Research, 2025)

Unlocking the Neuroprotective Potential of Silymarin: A Promising Ally in Safeguarding the Brain from Alzheimer’s Disease and Other Neurological Disorders - Abdulmajeed G. Almutary; M. Yasmin Begum; Ayesha Siddiqua; Saurabh Gupta; Payal Chauhan; Karan Wadhwa; Govind Singh; Danish Iqbal; Gopalakrishnan Padmapriya; Sanjay Kumar; Navin Kedia; Rajni Verma; et al. (Molecular Neurobiology, 2025)

Validation of AERMOD Prediction Accuracy for Particulate Matters (PM10, PM2.5) for a Large Coal Mine Complex: A Multisource Perspective - Navin Prasad; Akash Mishra; Tanushree Bhattacharya; Bindhu Lal; Prakash Chandra Jha; Abhishek Kumar (Aerosol Science and Engineering, 2025)

Strategy for Circularity Enhancement in Bioeconomy Sector: A Case Study from Biogas Sector of Nepal - Navin Kumar Jha; Brijesh Mainali; Sunil Prasad Lohani (Circular Economy and Sustainability, 2024)

Potential and Limitation of Peptides from Native Plants of Uttarakhand - Neha Kamboj; Rahul Kumar; Navin Kumar; Pankaj Gautam (International Journal of Peptide Research and Therapeutics, 2024)

Mechanistic insights into antifungal potential of Alexidine dihydrochloride and hexachlorophene in Candida albicans: a drug repurposing approach - Ayesha Ansari; Darshan Kumar; Payal Gupta; Krishna Mohan Poluri; Nishant Rai; Faud Ameen; Navin Kumar (Archives of Microbiology, 2024)

Extraction of anthocyanin from Hibiscus rosa-sinensis and concentration by forward osmosis membrane process - Atreyee Bal; H.N. Shilpa; Sukumar Debnath; Navin Kumar Rastogi (Innovative Food Science & Emerging Technologies, 2024)

Alternate solvent for soybean oil extraction based on extractability and membrane solvent recovery - Deepali Shejawale; Jyoti Lavania; Nageswaran Muthuganesan; Thangaraj Jeyarani; Navin Kumar Rastogi; Rangaswamy Subramanian (Environmental Science and Pollution Research, 2024)

On the response of the mesopause region over an Indian Antarctic station Bharati to the geomagnetic storm of 23–24 March 2023 - Navin Parihar; Anand Kumar Singh; Saranya Padincharapad; Shailendra Saini (Polar Science, 2024)

Screening of chemical composition of black soybean hulls: a comparative study of different extraction techniques - Palmei Gaibimei; Anupama Singh; Navin Chandra Shahi; Khan Chand; Sanjay Kumar; Prabhakar Semwal; Taghrid S. Alomar; Najla Al Masoud; Abdur Rauf (Plant Biosystems, 2024)

In vitro studies of epicotyl and embryo culture in cultivated, wild and inter-specific hybrids of okra (Abelmoschus spp.) - Bhargav S. Kiran; Ramesh Kumar Yadav; Suman Lata; Brij Bihari Sharma; A. Talukdar; Amalendu Ghosh; Navin Chandra Gupta; Bhoopal Singh Tomar (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Characterization of sub-tropical maize (Zea Mays L.) inbred lines for the variation in kernel row numbers (KRNs) - Ganapati Mukri; R. N. Gadag; Jayant S. Bhat; T. Nepolean; Navin C. Gupta; Shikha Mittal; M. L. Nithyashree; Ramesh Kumar; Digvender Pal (Cereal Research Communications, 2024)

Control efficacy and yield response of different fungicides evaluated against anthracnose of green gram - C.V. Nandeesha; L.F. Akbari; Aman Jaiswal; B.R. Harsha; Balanagouda Patil; C.M. Bhaliya; Navin kumar; Tribhuwan Singh; Sinchana Jain (Crop Protection, 2023)

Nitrogen dose dependant changes in grain morphology parameters are correlated with grain protein and yield traits in field-grown diverse rice genotypes - Birendra K. Padhan; Lekshmy Sathee; Santosh Kumar; Manoranjan Senapati; Viswanathan Chinnusamy; S. Gopala Krishnan; Dinesh Kumar; Navin Chandra Gupta; Arvind Kumar (Plant Physiology Reports, 2023)

Fabrication of HA Nano-crystal Reinforced PHAs based composites for orthopedic fracture-fixing accessories using sustainable resources - Preeti Tomer; Gireesh Kumar Shroti; Swati Mohapatra; Debashish Ghosh; Satish Jaiswal; Deepa Garg; Debrupa Lahiri; Navin Kumar; Om P. Khatri; Saugata Hazra (Environment, Development and Sustainability, 2023)

Reducing Arsenic Uptake in Cereal Crop Plants with Sugarcane Waste Application: A Comparative Study on the Effects on Physiology, Biochemistry, and Grain Nutrient Status - Ambedkar Gautam; Nikita Basant; Navin Kumar; Kriti; Shiv Naresh Singh; Arvind Kumar Dubey; Gayatri Singh; Babita Kumari; Kavita Shah; Shekhar Mallick (Journal of Plant Growth Regulation, 2023)

A thermodynamic model of integrated liquid-to-liquid thermoelectric heat pump systems - Hanlong Wan; Kyle R. Gluesenkamp; Bo Shen; Zhenning Li; Viral K. Patel; Navin Kumar (International Journal of Refrigeration, 2023)

Design & synthesis of hybrid pharmacophore of β-lactam, 1,8-naphthyridine, and secondary amines; Discover their in vitro antimicrobial, anticancer properties & DFT and ADMET prediction studies - Keyur M. Pandya; Satyanarayana Battula; K. A. Aravinda Kumar; Rajesh J. Patel; Navin B. Patel (Medicinal Chemistry Research, 2023)

Concentration of pomegranate juice by forward osmosis or thermal evaporation and its shelf-life kinetic studies - Das Trishitman; Pradeep Singh Negi; Navin Kumar Rastogi (Food Chemistry, 2023)

Evaluation of the Datura peels derived biochar-based Anode for enhancing power output in microbial fuel cell application - Anusha Vempaty; Ankit Kumar; Soumya Pandit; Meenal Gupta; Abhilasha Singh Mathuriya; Dibyajit Lahiri; Moupriya Nag; Yogesh Kumar; Sanket Joshi; Navin Kumar (Biocatalysis and Agricultural Biotechnology, 2023)

Temporal Modulation of DNA Methylation and Gene Expression in Monolayer and 3D Spheroids of Dental Pulp Stem Cells during Osteogenic Differentiation: A Comparative Study - Shalini Raik; Reetu Thakur; Vidya Rattan; Navin Kumar; Arnab Pal; Shalmoli Bhattacharyya (Tissue Engineering and Regenerative Medicine, 2022)

Role of ADME gene polymorphisms on imatinib disposition: results from a population pharmacokinetic study in chronic myeloid leukaemia - Bharati Shriyan; Parsshava Mehta; Anand Patil; Shraddha Jadhav; Sharath Kumar; Apeksha S. Puri; Ravina Govalkar; Manjunath Nookala Krishnamurthy; Sachin Punatar; Anant Gokarn; Navin Khattry; Vikram Gota (European Journal of Clinical Pharmacology, 2022)

Genomic selection for spot blotch in bread wheat breeding panels, full-sibs and half-sibs and index-based selection for spot blotch, heading and plant height - Philomin Juliana; Xinyao He; Jesse Poland; Krishna K. Roy; Paritosh K. Malaker; Vinod K. Mishra; Ramesh Chand; Sandesh Shrestha; Uttam Kumar; Chandan Roy; Navin C. Gahtyari; Arun K. Joshi; et al. (Theoretical and Applied Genetics, 2022)
Key message Genomic selection is a promising tool to select for spot blotch resistance and index-based selection can simultaneously select for spot blotch resistance, heading and plant height. Abstract A major biotic stress challenging bread wheat production in regions characterized by humid and warm weather is spot blotch caused by the fungus Bipolaris sorokiniana . Since genomic selection (GS) is a promising selection tool, we evaluated its potential for spot blotch in seven breeding panels comprising 6736 advanced lines from the International Maize and Wheat Improvement Center. Our results indicated moderately high mean genomic prediction accuracies of 0.53 and 0.40 within and across breeding panels, respectively which were on average 177.6% and 60.4% higher than the mean accuracies from fixed effects models using selected spot blotch loci. Genomic prediction was also evaluated in full-sibs and half-sibs panels and sibs were predicted with the highest mean accuracy (0.63) from a composite training population with random full-sibs and half-sibs. The mean accuracies when full-sibs were predicted from other full-sibs within families and when full-sibs panels were predicted from other half-sibs panels were 0.47 and 0.44, respectively. Comparison of GS with phenotypic selection (PS) of the top 10% of resistant lines suggested that GS could be an ideal tool to discard susceptible lines, as greater than 90% of the susceptible lines discarded by PS were also discarded by GS. We have also reported the evaluation of selection indices to simultaneously select non-late and non-tall genotypes with low spot blotch phenotypic values and genomic-estimated breeding values. Overall, this study demonstrates the potential of integrating GS and index-based selection for improving spot blotch resistance in bread wheat.

Genetic variability, combining ability and molecular diversity-based parental line selection for heterosis breeding in field corn (Zea mays L.) - Ganapati Mukri; Meghashri S Patil; Babu N Motagi; Jayant S Bhat; Chandu Singh; S. P. Jeevan Kumar; R. N Gadag; Navin C Gupta; Jesus Simal-Gandara (Molecular Biology Reports, 2022)
Background The demand of maize crop is increasing day by day, hence to reduce the production and demand gap, there is a need to extract the high yielding parental lines to improve per se yield of the hybrids, which could help to enhance the productivity in maize crops. Methods and results The present investigation was carried out to select the best medium maturing inbred lines, among a set of 118 inbred lines. Based on the Duncan multiple range test, out of 118 lines, 16 inbred lines were selected on the basis of its high yield per se and flowering time. The molecular diversity was carried out using SSR markers linked to heterotic QTL and up on diversity analysis it classified selected genotypes in to three distinct groups. Among the selected inbred lines, a wider genetic variability and molecular diversity were observed. A total of 39 test crosses were generated after classifying 16 inbred lines in to three testers and thirteen lines (based on per se grain yield and molecular diversity) and crossing them in line × tester manner. Conclusion Combining ability analysis of these parental lines showed that female parents, PML 109, PML 110, PML 111, PML 114 and PML 116 showed additive effect for KRN and grain yield, whereas male parents, PML 46, and PML 93 showed epistatic effect for KRN and PML 102 showed epistatic effect for grain yield. The generated information in the present investigation may be exploited for heterosis breeding in filed corn. Key messages To tackle the balanced dietary requirement of Indian population; we focused to enhance the productivity of maize hybrids using genetically broad based, elite, diverse inbred lines. Combination of selection criterion, not only augment the productivity but also improves the quality of hybrid/s.

Hexavalent Chromium and Male Reproduction: An Update - Ajit Kumar Navin; Mariajoseph Michael Aruldhas (Proceedings of the Zoological Society, 2021)

Over-expression of chickpea metallothionein 1 gene confers tolerance against major toxic heavy metal stress in Arabidopsis - Arvind Kumar Dubey; Anil Kumar; Navin Kumar; Sanoj Kumar; Meenakshi; Ambedkar Gautam; Mohd Akram Ansari; N. Manika; Swati Lal; Soumit Kumar Behera; Shekhar Mallick; Indraneel Sanyal (Physiology and Molecular Biology of Plants, 2021)

Genetic dissection of physiological traits over trait based breeding in bread wheat conferring terminal heat tolerance - Devender Sharma; Jai Prakash Jaiswal; Navin Chander Gahtyari; Anjana Chauhan; Narendra Kumar Singh (Cereal Research Communications, 2021)

Development and Evaluation of In Situ Gel of Silver Sulfadiazine for Improved Therapeutic Efficacy Against Infectious Burn Wound - Navin Joshi; Neeraj Mishra; Vineet Kumar Rai (Journal of Pharmaceutical Innovation, 2021)

Excitation light-induced phototoxicity during fluorescence imaging - Abhilasha Ojha; Navin Kumar Ojha (Journal of Biosciences, 2021)

Road Centerline Extraction From VHR Images Using SVM and Multi-Scale Maximum Response Filter - Pramod Kumar Soni; Navin Rajpal; Rajesh Mehta (Journal of the Indian Society of Remote Sensing, 2021)

On the interaction of mesoscale eddies and a tropical cyclone in the Bay of Bengal - Kumar Ravi Prakash; Tanuja Nigam; Vimlesh Pant; Navin Chandra (Natural Hazards, 2021)

Impact on endangered Gangetic dolphins due to construction of waterways on the river Ganga, India: an overview - Devina Aggarwal; Navin Kumar; Venkatesh Dutta (Environmental Sustainability, 2020)

Semiautomatic Road Extraction Framework Based on Shape Features and LS-SVM from High-Resolution Images - Pramod Kumar Soni; Navin Rajpal; Rajesh Mehta (Journal of the Indian Society of Remote Sensing, 2020)

A repertoire of high-affinity monoclonal antibodies specific to S. typhi: as potential candidate for improved typhoid diagnostic - Chandresh Sharma; Anurag Sankhyan; Tarang Sharma; Naeem Khan; Susmita Chaudhuri; Niraj Kumar; Shinjini Bhatnagar; Navin Khanna; Ashutosh Tiwari (Immunologic Research, 2015)

H2O2 pretreated rice seedlings specifically reduces arsenate not arsenite: difference in nutrient uptake and antioxidant defense response in a contrasting pair of rice cultivars - Shekhar Mallick; Navin Kumar; Sarita Sinha; Arvind Kumar Dubey; Rudra Deo Tripathi; Vivek Srivastav (Physiology and Molecular Biology of Plants, 2014)

Reduced Lantadenes A and B: semi-synthetic synthesis, selective cytotoxicity, apoptosis induction and inhibition of NO, TNF-α production in HL-60 cells - Suthar Sharad Kumar; Navin Tailor; Hong Boon Lee; Manu Sharma (Medicinal Chemistry Research, 2013)

Homologous Recombination is Activated at Early Time Points Following Exposure to Cobalt Chloride Induced Hypoxic Conditions in Saccharomyces cerevisiae - Ramesh Chand Meena; Navin Kumar; Surendra Nath; Amitabha Chakrabarti (Indian Journal of Microbiology, 2012)

Over-Expression of YLR162W in Saccharomyces cerevisiae Inhibits Cell Proliferation and Renders Cells Susceptible to the Hypoxic Conditions Induced by Cobalt Chloride - Navin Kumar; Ramesh C. Meena; Amitabha Chakrabarti (Indian Journal of Microbiology, 2011)

Modernizing Sarda Sahayak canal system: The Masscote approach - Ravindra Kumar; Navin Shukla; D. P. Nigam; V. K. Verma (Irrigation and Drainage, 2010)
Mapping system and services of canal management, operation and maintenance aims (a) to enable decision makers, before engaging in investment plans, to ensure that diagnosis and solutions are investigated properly in irrigation modernization projects (through a rapid appraisal procedure); and (b) to suggest some specific strategies on how one should make the best use of the modernization investment made currently (mapping system and services for canal operation techniques). On the basis of analysis carried out through a Food and Agriculture Organization (FAO) and Uttar Pradesh Irrigation Department (UPID) training workshop on 7–19 December 2007 for the Jaunpur Branch Canal (JBC) system of the Sarda Sahayak Irrigation Scheme, this paper describes what more needs to be done for modernizing irrigation management in JBC and in other command areas of the state. Some suggestions are: (i) recycling water through shallow wells in the area close to the canal to reduce waterlogging; (ii) formation of a federation of Water Users Associations (WUA) to reduce the cost of operation; (iii) installation of more cross‐regulators in the branch canal to run the canal at the designed full supply level; (iv) installation of modular gates for distributaries and minors; (v) periodic calibration of measurement structures; and (vi) modernization of inner and outer cross‐sections of the canal to attain their water‐carrying capacity. Copyright © 2010 John Wiley & Sons, Ltd.

Altered PPARγ expression inhibits myogenic differentiation in C2C12 skeletal muscle cells - Jaskirat Singh; Navin Kumar Verma; Sejal M. Kansagra; Bhusan N. Kate; Chinmoy Sankar Dey (Molecular and Cellular Biochemistry, 2007)